Uso da imunocastração como alternativa à castração cirúrgica na produção de novilhos para abate - Machado, Diego Soares (2015)
The objective of this study was to evaluate the use of immunological castration as an alternative to surgical castration in the production of beef cattle. In the research were used 48 Aberdeen Angus male bovines, monitored from initial age of six months and initial average weight of 160 kg at weaning. The animals were randomly distributed in the following treatments: surgically castrated at birth; surgically castrated at weaning; immunocastrated Bopriva® with three doses of vaccine, and immunocastrated Bopriva® with four doses of vaccine. The experimental design used was the completely randomized, with 12 replications. Means were classified by F test and compared by Tukey test with α=.05. There was interaction between date of sampling and treatment for serum testosterone levels in the blood plasma, however at slaughter all steers kept only residual levels of testosterone, characterized as castrated. Steers immunocastrated with three applications of Bopriva® had higher daily weight gain and total weight gain in the finishing phase, in relation to surgically castrated at weaning. However, throughout the evaluation stages, the performance was similar between treatments (P>.05). Steers castrated at birth had higher fat thickness to when adjusted 100 kg of cold carcass and lower chilling loss than castrated immunologically with three doses (P<.05). Immunocastration with three doses of Bopriva® provided increment in muscle participation in relation to surgically ones at both ages, and muscle: bone ratio in relation to castrated at weaning. It also reduced the participation of fat in relation to castrated at birth. Total internal organs in percentage of empty body weight, differ between the two immunocastration protocols, with superiority when applied four doses (3.61 vs 3.39 kg). Steers surgically castrated at birth showed superiority in the sum of sum of internal, toilet and kidney fats, for immunocastrated with three doses, regardless of the way it was expressed. The immunological castration proved to be a viable alternative to surgical castration, not changing the main parameters of economic interest and meat quality attributes, and promotes animal welfare, eliminating the surgery.